2022
DOI: 10.1101/2022.05.17.22275027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized Phase 2/3 Study of Ensitrelvir, a Novel Oral SARS-CoV-2 3C-like Protease Inhibitor, in Japanese Patients With Mild-to-Moderate COVID-19 or Asymptomatic SARS-CoV-2 Infection: Results of the Phase 2a Part

Abstract: For the treatment of coronavirus disease 2019 (COVID-19), antiviral agents that can achieve rapid severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reduction are warranted. This double-blind, phase 2a part of a phase 2/3 study assessed the efficacy and safety of ensitrelvir, a novel oral SARS-CoV-2 3C-like protease inhibitor, in Japanese patients with mild-to-moderate COVID-19 or asymptomatic SARS-CoV-2 infection. Sixty-nine patients enrolled from 56 sites were randomized (1:1:1) to orally receive 5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…In the current phase 2b part, virologic efficacy was assessed using the change in SARS-CoV-2 viral titer from baseline to day 4 (co-primary endpoint) and SARS-CoV-2 RNA (endpoint commonly used in clinical studies for anti–COVID-19 treatments 14, 16, 21 ). The rapid and significant reduction in the SARS-CoV-2 viral titer and viral RNA following ensitrelvir treatment is consistent with the findings of the previous phase 2a part 20 , but the level of viral titer reduction from baseline to day 4 was lower in the current phase 2b part (−1.49 log 10 TCID 50 /mL) than in the phase 2a part (−2.81 log 10 TCID 50 /mL with ensitrelvir 250 mg) 20 . These differences in findings may be attributed to the lower baseline titer recorded in the phase 2b part than in the phase 2a part (2.5–2.8 versus 3.3–3.7 log 10 TCID 50 /mL), as well as other unidentified differences in viral characteristics.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In the current phase 2b part, virologic efficacy was assessed using the change in SARS-CoV-2 viral titer from baseline to day 4 (co-primary endpoint) and SARS-CoV-2 RNA (endpoint commonly used in clinical studies for anti–COVID-19 treatments 14, 16, 21 ). The rapid and significant reduction in the SARS-CoV-2 viral titer and viral RNA following ensitrelvir treatment is consistent with the findings of the previous phase 2a part 20 , but the level of viral titer reduction from baseline to day 4 was lower in the current phase 2b part (−1.49 log 10 TCID 50 /mL) than in the phase 2a part (−2.81 log 10 TCID 50 /mL with ensitrelvir 250 mg) 20 . These differences in findings may be attributed to the lower baseline titer recorded in the phase 2b part than in the phase 2a part (2.5–2.8 versus 3.3–3.7 log 10 TCID 50 /mL), as well as other unidentified differences in viral characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…The current phase 2b part of the study found no clear dose response, which is consistent with the findings of the phase 2a part 20 . Pharmacokinetic data for 5-day ensitrelvir 125 mg treatment (375 mg on day 1) derived from the phase 1 study of ensitrelvir (maximum plasma concentration, 30.4 µg/mL; area under the curve, 598.3 µg•hr/mL) suggest that this regimen is sufficient to achieve a reduction in SARS-CoV-2 in humans (R. Shimizu et al, unpublished data).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations